Fiscal policy, inequality and welfare - Amiel, Yoram; Bishop, John A. (Emerald, 2003)
Research on Economic Inequality, Volume 10, Fiscal Policy, Inequality and Welfare contains ten papers, both theoretical and applied, on tax progressivity and tax and transfer equity. Theory topics covered include consumption tax equity, alternative definitions of tax progressivity, horizontal equity and reranking. The applied work includes studies of Australia's consumption taxes, Israel's national insurance tax system, Mexican transfer system, Canadian tax equity, trends in US tax and transfer progressivity and a study of the impact of the repeal of the US marriage tax penalty.
Keywords: Fiscal policy.; Equality.; Public welfare.; elektronické knihy; electronic books